A Novel SCB Test for Determining Fracture Quantities of Bituminous Composites - Ince, Ragip; Furtana, B. Fatih (ISRES Publishing, 2025)
Numerous non-Hookean fracture methods have been introduced to evaluate fracture parameters in quasi-brittle materials. In concrete structures, the effective crack model is widely used, and it requires determining the effective crack length and fracture toughness. Similarly, bituminous mixtures, which display ductile behavior at room temperature and brittle characteristics in colder conditions, demand non-Hookean fracture mechanics for accurate modeling due to defects like cracks and voids. This study focuses on assessing the fracture behavior of pure bituminous mixtures through experimental analysis. Ten semi-circular bending (SCB) specimens with varying initial crack lengths were prepared and subjected to three-point bending tests to capture load-displacement responses. The effective crack model, combined with the compliance technique, was utilized to calculate the fracture toughness of these samples. Findings aim to enhance understanding of fracture mechanisms in bituminous mixtures, contributing to the development of more durable pavements, especially under varying environmental conditions that influence material brittleness or ductility. © 2025 Published by ISRES Publishing: www.isres.org.
5th International Conference on Basic Sciences and Technology, ICBAST 2025 -- 28 August 2025 through 31 August 2025 -- Budapest -- 344359
Keywords: Bituminous composites; Effective crack model; Fracture mechanics; Semi-circular bending test